Evaluation of Oriented Strand Board Made from Rubberwood Using Phenol Formaldehyde as a Binder - Misran, Suffian (2005)
This study evaluates the potential of rubberwood to be used as raw material for the manufacture of oriented strand board (OSB). The logs were flaked using a disc flaker at a fixed length (152 mm). The resulting strands were examined for quality and physical appearance such as curliness, slenderness, dimensions and screening analysis. The strands were used for OSB manufacture and bonded using four types of phenol formaldehyde (PF) resins labelled as L1, L2, C1 and C2. The study shows that about 79% of the strands have size of bigger than 22 x 22 mm wire mesh. The strands have an average length of 69 mm, width 35 mm and thickness 0.6 mm. The edges of the strands were mostly not perpendicular with the adjacent surface which attributed by the deviation in cutting angle of the disc flaker. Most of the strands curled immediately after they came out from the disc flaker. The study also established five categories of curling: (1) flat, (2) curl and quarter round, (3) curl and half round, (4) curl and round, (5) curl and rolled. Almost half of the total strands produced can be grouped under curl classes 3, 4 and 5. It was observed that thicker strands are wider. However, strands with thickness of more than 0.5 mm has tendency to break into halves producing a lot of narrow strands. The strands have high slenderness and aspect ratios, averaged at 123 and 2.4 respectively. The degree of curling of rubberwood strands was small in thicker strands, while in wider strands, the degree of curling is higher. Pre-soaking of rubberwood billets in water for 24 hours prior to flaking did not give significant different in length, width and curliness with strands from unsoaked rubberwood billets. The modulus of rupture (MOR), modulus of elasticity (MOE) and internal bond (IB) improved with the increasing of board density. The thickness swelling (TS) was low on boards with low board density. On the other hand, these boards absorbed more water than do higher density boards. Increasing the resin level during board manufacture did not give much significant contribution to the MOE and MOR of the boards. Good IB value was achieved when 5% resin level was used. The swelling of boards can be reduced significantly by increasing the resin level to 5%. The type of PF resins used for bonding rubberwood strands has significant influence on the strength properties of rubberwood OSB. Significantly high MOE, MOR and IB values were obtained with C2 resin used at 7%. Whilst, boards bonded with L2 resin had very high TS.